2018
DOI: 10.1007/s00381-018-3961-0
|View full text |Cite
|
Sign up to set email alerts
|

Fracture related ulnar and sciatic nerve transections: a report of two cases and literature review

Abstract: Nerve laceration accompanying traumatic fracture is rare. We review the reported cases of nerve laceration and present two cases treated at our institution. Though uncommon, nerve laceration should be considered in the setting of traumatic fracture with neurological injury, particularly open fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
5
0
2
Order By: Relevance
“…Studies have shown poor results with nerve graft repair of transected sciatic nerve, both at the buttock and thigh level, particularly in adult patients (although pediatric patients tend to do better). 3,15,16 In this case particularly, given the >7-cm gap and the proximal site of injury, we felt that using autograft from bilateral sural nerves would yield limited recovery. What we found in this case was that our patient tolerated the femur shortening, insertion of growing rod, and subsequent removal very well.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies have shown poor results with nerve graft repair of transected sciatic nerve, both at the buttock and thigh level, particularly in adult patients (although pediatric patients tend to do better). 3,15,16 In this case particularly, given the >7-cm gap and the proximal site of injury, we felt that using autograft from bilateral sural nerves would yield limited recovery. What we found in this case was that our patient tolerated the femur shortening, insertion of growing rod, and subsequent removal very well.…”
Section: Discussionmentioning
confidence: 96%
“…In the setting of sciatic nerve transections occurring proximally in the thigh or buttocks, prognosis is poor. 3,15,16 Novel treatment algorithms in this setting may lead to better outcomes. In this article, we present a novel technique involving femur shortening, followed by insertion of an expandable rod to facilitate direct end-to-end tension-free sciatic nerve repair.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Liegt bildgebend der dringende Verdacht für eine Durchtrennung oder ein Kontinuitätsneurom vor, ist eine baldige operative Versorgung anzustreben [8,10,[13][14][15] In der hier untersuchten Kohorte betrug der durchschnittliche Zeitraum bis zur chirurgischen Freilegung 122,2 ± 85 Tage und folgt damit dieser Empfehlung.…”
Section: Diskussionunclassified
“…Fractures have a negative impact on children and young people in multiple ways. [19][20][21][22][23][24][25] Given the increasing trend of methylphenidate uses all over the world over the past 20 years, 3,26 it is necessary to understand the relationship between the risk of fractures and methylphenidate use, to address the knowledge gap and to provide clinical guidance. Although several observational studies using between-subject design 17,18,27,28 have been conducted to investigate the association between the use of methylphenidate and the risk of fractures, they have yielded mixed results.…”
Section: Introductionmentioning
confidence: 99%